2014
DOI: 10.1038/ncomms4996
|View full text |Cite
|
Sign up to set email alerts
|

ER–mitochondria associations are regulated by the VAPB–PTPIP51 interaction and are disrupted by ALS/FTD-associated TDP-43

Abstract: Mitochondria and the endoplasmic reticulum (ER) form tight structural associations and these facilitate a number of cellular functions. However, the mechanisms by which regions of the ER become tethered to mitochondria are not properly known. Understanding these mechanisms is not just important for comprehending fundamental physiological processes but also for understanding pathogenic processes in some disease states. In particular, disruption to ER–mitochondria associations is linked to some neurodegenerative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
614
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 500 publications
(672 citation statements)
references
References 59 publications
33
614
2
Order By: Relevance
“…ERMES, a homolog of which has not yet been identified in higher eukaryotes, was suggested to be involved in phospholipid exchange, calcium signaling, and mitochondrial physiology (70)(71)(72). Recently, ER-mitochondrion contact sites have been shown to play a role in neurodegenerative diseases like Alzheimer's disease and amyotrophic lateral sclerosis (73,74).…”
Section: Figmentioning
confidence: 99%
“…ERMES, a homolog of which has not yet been identified in higher eukaryotes, was suggested to be involved in phospholipid exchange, calcium signaling, and mitochondrial physiology (70)(71)(72). Recently, ER-mitochondrion contact sites have been shown to play a role in neurodegenerative diseases like Alzheimer's disease and amyotrophic lateral sclerosis (73,74).…”
Section: Figmentioning
confidence: 99%
“…Abnormal mitochondrial ultrastructure is also observed in SOD1 mutant mice, which may cause defects in mitochondrial trafficking (Magrané et al, 2009) Additionally, aberrant interaction of mutant SOD1 with OMM proteins such as VDAC1 can cause mitochondrial damage, and mutant SOD1 aggregates accumulate inside mitochondria causing oxidative stress (Palomo and Manfredi, 2015). Mutant TDP-43 conversely, forms aggregates which reduce contacts sites between mitochondria and the endoplasmic reticulum, possibly through and interaction with Mfn-2 (Stoica et al, 2014;Wang et al, 2013). Perturbations to these contacts sites lead to deregulation of mitochondrial Ca 2+ homeostasis.…”
Section: Mitochondrial Dysfunction In Neurodegenerationmentioning
confidence: 99%
“…[86][87][88][89][90] Murine models have illustrated loss of function mutations altering the unfolded protein response pathway, reducing functional myotubule formation 91 and this model has been illustrated in human samples elsewhere. 86,92 Additional murine studies have demonstrated progressive hyperactivity and motor impairment due to corticospinal and spinal motor neuron destruction in VABP transgenic mice.…”
Section: P56s-vesicle-associated Membrane Protein-associated Proteinmentioning
confidence: 99%